2001
DOI: 10.1074/jbc.m100157200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Helicase Activity of eIF4A by eIF4B, eIF4H, and eIF4F

Abstract: Eukaryotic initiation factor (eIF) 4A is a DEAD box RNA helicase that works in conjunction with eIF4B, eIF4H, or as a subunit of eIF4F to unwind secondary structure in the 5-untranslated region of mRNA, which facilitates binding of the mRNA to the 40 S ribosomal subunit. This study demonstrates how the helicase activity of eIF4A is modulated by eIF4B, eIF4H, or as a subunit of eIF4F. Results indicate that a linear relationship exists between the initial rate or amplitude of unwinding and duplex stability for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
278
3
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 309 publications
(301 citation statements)
references
References 48 publications
18
278
3
2
Order By: Relevance
“…The eIF4G-induced, half-open form of eIF4A promotes RNA binding and also accelerates phosphate release, which is presumably the rate-limiting step in the ATPase cycle for eIF4A 91 . These findings are consistent with the well-documented stimulation of the RNA-dependent ATPase activity of eIF4A by eIF4G 85 . In addition, full-length eIF4G might also increase binding of eIF4A to RNA by providing additional RNAbinding sites 85 .…”
Section: Nuclear Specklessupporting
confidence: 91%
See 2 more Smart Citations
“…The eIF4G-induced, half-open form of eIF4A promotes RNA binding and also accelerates phosphate release, which is presumably the rate-limiting step in the ATPase cycle for eIF4A 91 . These findings are consistent with the well-documented stimulation of the RNA-dependent ATPase activity of eIF4A by eIF4G 85 . In addition, full-length eIF4G might also increase binding of eIF4A to RNA by providing additional RNAbinding sites 85 .…”
Section: Nuclear Specklessupporting
confidence: 91%
“…These findings are consistent with the well-documented stimulation of the RNA-dependent ATPase activity of eIF4A by eIF4G 85 . In addition, full-length eIF4G might also increase binding of eIF4A to RNA by providing additional RNAbinding sites 85 . A further study indicated that eIF4G promotes the formation of a complex of eIF4A, eIF4B and RNA 92 .…”
Section: Nuclear Specklessupporting
confidence: 91%
See 1 more Smart Citation
“…A similar enhancement in activity has been reported for the eukaryotic eIF4A DEAD box helicase upon binding to its adaptor protein eIF4G, which forms part of a larger multienzyme complex involved in translation initiation (11). NMR studies have indicated that the site of interaction for eIF4G is on the C-terminal domain of eIF4A (44).…”
Section: Discussionmentioning
confidence: 56%
“…The ATP-dependent helicase activity of recombinant or purified eIF4AI is weak; however, the RNA helicase activity of eIF4AI is stimulated by cofactors, such as eIF4B and eIF4H (43)(44)(45). Like eIF4AI, purified eIF4AIII has relatively weak helicase activity (32,45,46).…”
Section: Discussionmentioning
confidence: 99%